Integrasi Sains Dan Agama Dalam Pendidikan Islam - Nasiruddin . (Universitas Alma Ata, 2013)
Discuss the issue of science and religion, we would come to the discussion of the interaction of science and religion at the same time meaningful symbolic level. In geneologis we can see the complexity of the interaction of religion and science in the debate between faith dimension textually understood and understand the marginalizing science because of religious doctrine often considered incompatible with the common sense arguments. Though science and religion born from the same womb that is the